Prevalence And Self-Knowledge Of Indicators Of Inflammation Suggestive of Periodontal Disease In Military Personnel - Ana Paula Porto Amorim Machado; André Ricardo Araújo da Silva; Licínio Esmeraldo da Silva (Portal de Periódicos da Marinha do Brasil, 2023)
The objective of this study was to identify the prevalence and self-recognition for indicators of inflammation suggestive of periodontal disease in military personnel of both genders. The military personnel was recruited to conduct a dental census for the entire population of the Admiral Wandenkolk Training Center of the Brazilian Navy, totaling 409 volunteers. Two groups were formed for further analysis: Group 1- containing exclusively women and Group 2- containing exclusively men. A total of 409 clinical examinations were performed and the questionnaires were analyzed. The results showed that, regarding the military participants, 40.1% were female and 59.9% were male; 87% used dental floss, of which 56% used it daily; 77% brushed three times a day or more; 74.3% reported that they visited the dentist regularly, and the proportion of women who regularly visited the dentist significantly exceeded the proportion of men who did (C.I. 95%; p<0.001); 61.6% said they knew about periodontal disease. The professional evaluation verified the presence of inflammation indicators suggestive of periodontal disease in 45.2% of the participants, of which 37% were female and 63% were male, with no statistical difference between genders (95% CI, p=0.2248). The prevalence of inflammation indicators suggestive of periodontal disease was 45.2%; the self-knowledge of the military about the periodontal disease was low, only 19%; thus a statistical difference was found between the knowledge of females and males; and it was observed that most participants were within the correct frequency for return visits to the dentist.